Focus on the Role of the NLRP3 Inflammasome in Multiple Sclerosis: Pathogenesis, Diagnosis, and Therapeutics - Cui, Yueran; Yu, Haiyang; Bu, Zhongqi; Wen, Lulu; Yan, Lili; Feng, Juan (Frontiers in Molecular Neuroscience, 2022)
Neuroinflammation is initiated with an aberrant innate immune response in the central nervous system (CNS) and is involved in many neurological diseases. Inflammasomes are intracellular multiprotein complexes that can be used as platforms to induce the maturation and secretion of proinflammatory cytokines and pyroptosis, thus playing a pivotal role in neuroinflammation. Among the inflammasomes, the nucleotide-binding oligomerization domain-, leucine-rich repeat- and pyrin domain-containing 3 (NLRP3) inflammasome is well characterized and contributes to many neurological diseases, such as multiple sclerosis (MS), Alzheimer's disease (AD), and ischemic stroke. MS is a chronic autoimmune disease of the CNS, and its hallmarks include chronic inflammation, demyelination, and neurodegeneration. Studies have demonstrated a relationship between MS and the NLRP3 inflammasome. To date, the pathogenesis of MS is not fully understood, and clinical studies on novel therapies are still underway. Here, we review the activation mechanism of the NLRP3 inflammasome, its role in MS, and therapies targeting related molecules, which may be beneficial in MS.